Pengaruh Budaya Literasi Terhadap Hasil Belajar Siswa KELAS IV Pada Pembelajaran IPA DI SD Negeri 091608 Sinaksak - Lamhot Tua Simanjuntak; Andriono Manalu; Ady Frendly Simanullang (CV. KAMPUS AKADEMIK PUBLISING, 2023)
This research aims to determine the influence of literacy culture on the learning outcomes of class IV students in science learning on the Energy Sources sub-theme at SD Negeri 091608 Sinaksak odd semester FY 2023/2024. The type of research in this research is quantitative research. The research population was all fourth grade students at SD Negeri 091608 Sinaksak totaling 30 students. The sampling technique in this research is non-probability sampling, where the sample selected is a saturated sample. The sample in this study consisted of class IV of state elementary school 091608 Sinaksak, totaling 30 students. The results of this research show that student learning outcomes apply literacy culture with an average score of 80.13. The results of the t distribution test at the significance level (ɑ = 0.05), dk = N-1 = 30-1 = 29, namely tcount>ttable, then the data has a t distribution with the result 18,371>ttable 2.045 data can be said to have a significant influence. The results of the t-test table prove that there is an influence of literacy culture (X) on learning outcomes (Y) with a tcount of 18.371>ttable 2.045. This proves that there is a significant influence of the application of literacy culture on class IV learning outcomes in the Energy Resources sub-theme at SD Negeri 091608 Sinaksak.